Induksi Metastasis Limfonodus oleh DMBA Topikal pada Model Mencit C3H/HeJ dengan Karsinoma Sel Skuamosa - Fitria Tahta Alfina; Devy Ariany; Nurlaely Mida Rachmawati; Luluk Hermawati; Ghina Mutiara Abas (Lembaga Pengembangan Kinerja Dosen, 2026)
7,12-Dimethylbenz(a)anthracene (DMBA) is an environmental carcinogen. Topical application of DMBA in mice induces skin tumors with 100% incidence, and approximately 40% progress to squamous cell carcinoma (SCC), which carries a high risk of metastasis. To evaluate lymph node metastasis in SCC following topical administration of 0.125% DMBA. This research was conducted as a laboratory experimental study A total of 200 µl of 0.125% DMBA was applied topically to the dorsal skin of C3H/HeJ mice three times a week for 10 weeks. All mice with SCC showed metastatic deposits in the lymph nodes, characterized by anaplastic cells with hyperchromatic nuclei and a 1:1 nucleus-to-cytoplasm ratio. Significant differences in follicular area were found between the malignant DMBA group and the vehicle (mean difference 0.26; P<0.001), distilled water (0.25; P<0.001), and between the benign DMBA group and both vehicle (0.28; P<0.001) and distilled water (0.27; P < 0.001). No significant differences were observed between the malignant and benign DMBA groups (P = 0.767), or between vehicle and distilled water (P = 0.884). Topical application of 0.125% DMBA for 10 weeks is associated with lymph node metastasis in SCC, which can be identified through histological observation of tumor cell deposits and follicular hyperplasia in lymph nodes.